Rethinking Orality II The Mechanisms of the Oral Communication System in the Case of the Archaic Epos - Ercolani, Andrea; Lulli, Laura (Transcodification: Arts, Languages and Media, 2022)
This is the second of two volumes on the mechanisms of oral communication in ancient Greece, focused on epic poetry, which had deep roots in orality. Combining the tools of cognitive science with the historical and literary analysis of the texts, this survey considers the traces of orality in archaic epic poetry and their adaptation in the changes that the comminicative system showed both synchronously and diachronically.